Faktor-Faktor yang Berhubungan dengan Pemberian Susu Formula dengan Kejadian Diare pada Bayi di Wilayah Kerja Puskesmas Tinondo Kabupaten Kolaka Timur Tahun 2015 - Firman, Firman; Ferawati, Ferawati (Jurnal Gizi Ilmiah, 2016)
Data from the Diarrhea Program of the Tinondo Health Center in East Kolaka Regency, patients with diarrheal disease aged 0-11 months (infants) were 43 cases. The purpose of this study was to determine the factors associated with formula feeding with the incidence of diarrhea in infants in the working area of ​​the Tinondo Health Center, East Kolaka Regency in 2015. This type of research is analytical using a cross sectional study design, a sample of 61 people using the proportional sampling technique. method of analysis using Chis - Square test . The results of the statistical test show that there is a relationship between the dependent variable and the independent variable with the value of each variable, Milk Bottle Hygiene (Xcount: 5.32 and Phi value: 0.295), Feeding Time (XCount: 5.07 and Phi value: 0.288), Type of Milk (XCount: 8.89 and Phi value: 0.382) with the incidence of diarrhea. It is hoped that the government will provide more information to the public on how to prepare the correct milk bottle, and the correct type of time to give formula milk.